Identifying circular economy strategies for decarbonization in built environment: A comparative analysis of key stakeholders in Vietnam - Nguyen Van Tam; Nguyen Quoc Toan; Pham Thi Thuy Duong (Sustainable Futures)
This study investigated 15 key circular economy strategies for decarbonization (CES4D) in the built environment by comparing the perspectives of key stakeholders. Data from 105 professionals in Vietnam were analyzed using various statistical techniques. The results revealed significant disparities in stakeholder perceptions of the key CES4D. The findings highlighted that top priorities include effective waste management, mandatory waste reduction targets, promotion of digital design tools, sustainable materials, and innovative design solutions. This research theoretically bridges the gap between circularity and decarbonization. It provides recommendations for policymakers and industry stakeholders to facilitate the transition toward a sustainable and circular built environment.